Analisis Isi dan Kelayakan Penyajian Buku Sekolah Elektronik (BSE) Mata Pelajaran Penjasorkes Kelas 2 Sekolah Dasar - Irsyada, Roas (Journal of Physical Education Health and Sport, 2016)
This research is descriptif kuantitatif with content analysis technic. The sample is 2 electronic book school PE for 2nd grade of primary school. The instrument is used in this research is the instrument of the text book. Based on the research that was done, it was shown that the feasibility content of the 1st electronic book school of PE (by Deni Kurniadi, Suro Prapanca) got score 155 which is in suitable criteria, 2nd book (by Pramono) got score 164 which is in criteria meanwhile the feasibility content 1st book got score 127 wihich in suitable and the 2nd got score 143 in very suitable.